DeepSeek-V3 Auxiliary-Loss-Free Routing for Long-Context Load Balancing Efficiency - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: How does the load balancing efficiency of DeepSeek-V3's auxiliary-loss-free policy compare to traditional routing methods during long-context inference tasks. 13 claims were extracted from source literature; 4 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.3/10. This report is a machine-generated literature synthe
Machine-generated literature synthesis.